Development of Smart Tree Learning Media for Ethnic Diversity Material to Increase Learning Motivation in Students - Ria Milawati; Azri Ranuwaldy Sugma; Zulham Siregar (research, training and philanthropy institution Natural Aceh, 2023)
This research is motivated by learning that still tends to use the method of explaining in the material on the theme of Environment learning objectives that have yet to be achieved optimally, affecting the effectiveness of student learning. One of the efforts that can be used is through smart tree learning media. This research uses research and Development (R&D) research methodology. Smart Tree Learning Media is carried out based on ADDIE development steps. Populusi in this study were 20 SD Negeri grade IV students 105286 Tandam Hilir 1. The results showed; (1) the material expert validity test got a score of 92% and was very well qualified, (2) The validity test of media experts got a score of 86.67% and was of very good qualifications, (3) the validity test of Class IV Teachers got a score of 90% was in very good qualifications, (4) individual trials got a score of 91.11% were in very good qualifications, Small Group trials got 90.13% were in very good qualifications, Large Group trials got 88% scores were in very good qualifications. The results showed a significant difference between students' learning outcomes using thematic Smart Tree learning media and conventional learning media.